Copper-based-zinc-boron foliar fertilizer improved yield, quality, physiological characteristics, and microelement concentration of celery (Apium graveolens L.). Issue 1 (1st January 2019) - Ma, Jin-Zhao; Zhang, Min; Liu, Zhi-Guang; Wang, Min; Sun, Yao; Zheng, Wen-Kui; Lu, Hao
ABSTRACT: Celery is one of the most widely cultivated vegetables worldwide. Boron (B), zinc (Zn), and copper (Cu) are essential microelements for plant growth with Cu also important in controlling fungal diseases. But little is known about the combined effects of B, Zn, and Cu fertilizers on celery. A pot experiment was conducted during two growing seasons (2014–2015 and 2015–2016) using a novel foliar fertilizer: a copper-based-zinc-boron foliar fertilizer (Cu-ZnB) based on the Bordeaux mixture (BDM). Celeries were sprayed with water (the control); BDM; 1.0, 1.5 and 2.0 g L −1 copper foliar fertilizer (CFF1, CFF2, and CFF3), and with 1.0, 1.5 and 2.0 g L −1 the Cu-ZnB (Cu-ZnB1, Cu-ZnB2, and Cu-ZnB3). During both seasons, Cu-ZnB1 increased celery yield and decreased disease index, compared with control and BDM treatments. Application of Cu-ZnB1 also increased vitamin C content while reducing nitrate content of celery compared with BDM and increased leaf Zn and B concentration compared with the control, BDM, and CFF1 treatments. Furthermore, Leaf Cu concentration in Cu-ZnB1 treatment was lower by 76.9% compared with BDM. Spraying Cu-ZnB1 also significantly increased SOD, POD, and CAT activities, while decreasing MDA content of functional leaves. By applying Cu-ZnB during 2015–2\016, soil available Cu concentration was reduced by 24.9–42.2%, compared with BDM. Hence, applying 1.0 g L −1 Cu-ZnB to celery is recommended for enhancing plant nutritional quality and yield; simultaneously, it reduces the levels of Cu in the soil and disease index of celery.